Economic expectations of Turkish youth from EU membership - Danışman, Efehan (My University, 2013)
TÜRK GENÇLERİNİN AVRUPA BİRLİĞİ’NDEN EKONOMİK BEKLENTİLERİ ÖZET Bu tez gençlerin Avrupa Birliği’nden (AB) beklentilerini, özel olarak da ekonomik beklentilerini analiz etmiştir. Tezin temel motivasyonu gençlerin AB algıları hakkında yeterli sayıda çalışma olmaması, Türkiye’nin genç nüfusu ve önümüzdeki aylarda hızlanacağı beklenen Türkiye’nin AB ile bütünleşme sürecidir. Çalışma İstanbul’da 485 örneklemle internet ve yüz yüze görüşmelerle 21 soruluk bir anketin katılımcılara yöneltilmesiyle gerçekleştirilmiştir. Sorular katılımcıların yaşı, cinsiyeti, geliri, doğduğu şehir, AB’nin imajı, AB üyeliğine olan inancı, AB’den ekonomik beklentileri ve AB ülkelerinde yaşama ve çalışma isteğini ölçmeyi amaçlamıştır. Sonuçlara göre gençler artık AB’yi eskisi gibi bir refah kaynağı olarak görmemekte ve AB’nin imajını nötr olarak bulmaktadır. Üniversite öğrencilerinin büyük bölümü Türkiye’nin hiçbir zaman AB’ye üye olamayacağına inanmaktadır. Bunun yanında katılımcıların büyük bölümü AB ülkelerinde yaşamak ve çalışmak istemektedir. Avrupa Birliği, kamuoyu, AB İktisadı ECONOMIC EXPECTATIONS OF TURKISH YOUTH FROM EU MEMBERSHIP

This thesis analyzed young people’s perception of the European Union (EU), their expectations from the EU membership and specifically economic expectations of the youth from the EU membership. Lack of sufficient studies on youth’s perception regarding the EU, specifically university students’, Turkey’s young population and EU integration process of Turkey which is expected to fasten during next months are main motivations behind this thesis. Study has been conducted with 485 samples through internet and face to face interviews in Istanbul. Attendees are asked 21 different questions concerning their age, gender, income, where they were born, EU’s image, belief to the EU membership, economic expectations from the EU membership and university students’ prospects to go and live in the EU countries. At the end of this analysis it has been found that university students have rather neutral EU image and do not see EU as source of prosperity as before. Most of them do not believe Turkey will ever be an EU member. Nonetheless, university students would like to go and live in the EU countries. Key words: European Union, public opinion, EU Economics
Keywords: Avrupa Birliği; Avrupa Birliği Ülkeleri; Ekonomi